2020
DOI: 10.1002/uog.20292
|View full text |Cite
|
Sign up to set email alerts
|

Placental DNA methylation changes in detection of tetralogy of Fallot

Abstract: Objectives To determine whether the methylation level of cytosine nucleotides in placental DNA can be used to predict tetralogy of Fallot (TOF) and provide insights into the developmental mechanism of this condition. Methods Tissue sections were obtained from formalin‐fixed paraffin‐embedded specimens of placental tissue obtained at birth from eight cases with non‐chromosomal, non‐syndromic TOF and 10 unaffected newborns. The Illumina Infinium HumanMethylation450 BeadChip assay was used to measure cytosine (‘C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…As a result, the cases of CHD that are detected before birth are usually detected well after the heart is malformed. Second, genome-wide analysis has identified distinct pathogenic mutations in only ~10% of cases [10,11,12,13,14,15,16,17,18]. While pathogenic gene mutations are likely involved in the remaining cases, epigenetics and mechanobiology may also cause CHD and certainly exacerbate defects and lead to pathogenic cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the cases of CHD that are detected before birth are usually detected well after the heart is malformed. Second, genome-wide analysis has identified distinct pathogenic mutations in only ~10% of cases [10,11,12,13,14,15,16,17,18]. While pathogenic gene mutations are likely involved in the remaining cases, epigenetics and mechanobiology may also cause CHD and certainly exacerbate defects and lead to pathogenic cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Placental tissue is a currently underutilized and non-invasive source of potential biomarkers for the postnatal diagnosis of CHD. One study found 166 CpG loci with differential methylation in placental tissue from TOF [17]. Epigenetic analysis of placentas from patients with VSD revealed 80 CpGs and eight miRNAs that had the potential to accurately detect VSD [170].…”
Section: Recent Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical and bioinformatic analyses were performed followed by data processing and quality control. A β-value based on the ratio of methylated and unmethylated signal intensities were calculated for each CpG loci using GenomeStudio software as detailed in our prior publications [12,22]. FDR (Benjamini-Hochberg) p-value < 0.05 was considered significant.…”
Section: Genome-wide Dna Methylation Profiling and Statistical Analysismentioning
confidence: 99%
“…Interestingly, the use of placental tissue to identify methylation markers in CHD has recently been explored as a potentially useful surrogate for evaluating the development of heart tissue. One study found 165 significantly differentially methylated CpG loci in 8 non-chromosomal, non-syndromic TOF cases compared with 10 unaffected newborns, in 165 separate genes [ 155 ]. Methylation analysis on placentas of 8 term subjects with isolated VSD and 10 unaffected controls revealed 80 CpGs and eight miRNAs that had the potential to accurately detect VSD [ 128 ].…”
Section: Epigenetics and Congenital Heart Diseasementioning
confidence: 99%